2021
DOI: 10.1152/ajpregu.00054.2021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute antioxidant supplementation on vascular function and autonomic nervous system modulation in young adults with PTSD

Abstract: PURPOSE: Posttraumatic stress disorder (PTSD) has been associated with an increase in risk of cardiovascular disease (CVD). The goal of the study was to determine if peripheral vascular dysfunction, a precursor to CVD, was present in young adults with PTSD, and if an acute antioxidant (AO) supplementation could modify this potential PTSD-induced vascular dysfunction. METHODS: Thirteen individuals with PTSD were recruited for this investigation and were compared to 35 age- and sex-matched controls (CTRL). The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Thirteen young, otherwise healthy adults with PTSD (nine female, four male) and 13 sex‐ and age‐matched healthy controls were recruited from Virginia Commonwealth University and the Richmond, Virginia metropolitan area to participate in this study. The PTSD group comprised the same participants who participated in a recently published study that identified microvascular dysfunction and SNS predominance at rest in this population (vs. healthy controls) (Weggen et al., 2021). Apart from subject demographics, no other data have been previously published.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen young, otherwise healthy adults with PTSD (nine female, four male) and 13 sex‐ and age‐matched healthy controls were recruited from Virginia Commonwealth University and the Richmond, Virginia metropolitan area to participate in this study. The PTSD group comprised the same participants who participated in a recently published study that identified microvascular dysfunction and SNS predominance at rest in this population (vs. healthy controls) (Weggen et al., 2021). Apart from subject demographics, no other data have been previously published.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work by our laboratory identified microvascular dysfunction in the arm and leg as well as autonomic nervous system imbalance in young (∼23 years) individuals with PTSD (Weggen et al, 2021), but as these measures were employed at rest it is unclear if these consequences of PTSD are robust enough to impact blood flow regulation during exercise, a hallmark characteristic of future hypertension and CVD development (Jae et al, 2015;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations